PENGARUH GREEN ACCOUNTING, SOLVABILITAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yunita Angelique; Siti Aisyah Nasution; Shevila Adithio; Vincent Colin Ongah; Keumala Hayati (JURNAL LENTERA BISNIS, 2025)
The value of a company is crucial because it reflects the company's performance, which can influence investor perceptions. However, in the long term, a company should not only focus on its value but also consider environmental issues that can affect its sustainability. This study aims to examine the effect of Green Accounting, Solvency, Accounts Receivable Turnover, and Inventory Turnover on the Company Value in the Mining Sub-Sector listed on the Indonesia Stock Exchange (IDX). The population consists of all objects to be investigated, which in this study amounts to 62 companies in the mining sub-sector listed on the IDX. The sample used in this study includes 22 companies over a period of 3 years, resulting in a total of 66 research samples. The findings show that Green Accounting has a negative and insignificant effect on the company value, Debt to Equity Ratio has a positive and significant effect on company value, Accounts Receivable Turnover does not have a significant effect on company value, and Inventory Turnover has a positive and significant effect on company value. Meanwhile, simultaneously, Institutional Ownership, Return on Assets, Return on Equity, Green Accounting, Debt to Equity Ratio, Accounts Receivable Turnover, and Inventory Turnover all have a positive and significant effect on company value.